2015
DOI: 10.1159/000381055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Automated Processing System (TACAS™ Pro) for Liquid-Based Procedures

Abstract: Objective: To evaluate a fully automated processing system (TACAS™ Pro) for liquid-based procedures (LBPs). Methods and Materials: Materials were 3,483 and additionally 502 specimens that were taken at Kanagawa Health Service Association. Specimens obtained with a Cervex-Brush® were first smeared to glass slides using one side of the brush and then processed to TACAS Pro. Results: (1) The microscopy watching time per normal case was 3.65 ± 0.85 min in the conventional procedure, whereas in the LBP it was 1.95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…These findings are similar to those for cervical cytology [11,12,13]. Kuramoto et al [11] reported that cells prepared with LBP shrunk by approximately 5% when granulocytes were compared in the specimens of both procedures.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are similar to those for cervical cytology [11,12,13]. Kuramoto et al [11] reported that cells prepared with LBP shrunk by approximately 5% when granulocytes were compared in the specimens of both procedures.…”
Section: Discussionsupporting
confidence: 82%
“…Liquid-based procedures (LBP) [5,6,7,8,9,10,11,12,13] for cervical cytology have become more widely used. This may be due to the clear cytological specimens obtained by the automated processing system in the limited field of glass slides.…”
Section: Introductionmentioning
confidence: 99%
“…After full‐text screening, 11 publications were excluded: five studies that did not adopt TBS, two studies that evaluated partially overlapping participants, one that assessed data from unclear settings, one that assessed data from hospital settings, one that assessed data from laboratory settings, and one review without original data. Finally, 17 studies (three direct, eight indirect, and one both comparison studies between CC and LBC, and five studies assessing CC only) including 1 497 451 unique healthy women were eligible.…”
Section: Resultsmentioning
confidence: 99%
“…No studies explicitly reported whether participants were prospectively enrolled or whether data were retrospectively assessed. Only three studies reported that the investigators consecutively evaluated the smear samples from a group of eligible subjects; the other 14 studies did not describe the consecutiveness of the assessed smear results. Eight studies were based on a single center's experience, whereas the other seven studies collected and assessed the pertinent data from multiple institutions (two studies not described).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation